Analysis of PSSDB wall panel with vertical butt joints in the dryboards / Hersaiful Herwan Baharuddin - Baharuddin, Hersaiful Herwan (Faculty of Civil Engineering, 2004)
Composite engineering component which may consist of two or more materials, connected or combined to give a performance in services, which is superior to the properties of its individual materials. Profiled steel sheet dry board (PSSDB) is a composite system, which classified into macro composite system comprises of profiled steel sheet, cemboard and connected by self-tapping screw. This system when combined imposed strength and stiffness. The proposed of this system as a load-bearing wall give more advantages in building construction. It’s a lightweight structure, easy to fabricate and save a lot of time for installation work. In this thesis research, Profile Steel Sheet Dry Board has been treated as load-bearing wall, where it’s due to window opening using finite element method (LUSAS) has been analyzed. The model analyzed measures 1200 mm wide and 1000 mm high. A window opening of 400 mm by 400 mm is modeled as symmetrical position. LUSAS 13.5 software adopted to create the finite element model. The model was modeling using 3D thin shell elements as a profiled steel sheet (Bondek II) and dry board (Cemboard). A series of load had been assign to this model and the result are stated as follow; for load 256 kN/m the maximum displacement is 2.838 mm, for maximum stress is - 541.5 N/mm2 and for the maximum strain is 0.0071.